DAMPAK TERHADAP TINDAKAN MEMPERTONTONKAN TERSANGKA DI MUKA UMUM DITINJAU DARI ASAS PRADUGA TAK BERSALAH - Yakobus Yakobus; R Rahaditya (Fakultas Hukum Universitas Tarumanagara, 2021)
The principle of presumption of innocence is regulated in Law No. 14 of 1970 Article 8 which contains the definition of the presumption of innocence. But this principle is often ignored by law enforcers in the investigation process in a variety of ways, one of which is the act of showing the suspect in public, cases like this have very often occurred in the investigation process in Indonesia, especially in the field of special crimes of corruption and narcotics. This has become an inherent culture for law enforcers to expose suspects to the public, with this action suspects who have not yet received a guilty verdict must undergo social sanctions obtained from showing this suspect, so that it can have an impact that can stick to the suspect. alone as well as relatives and family. Many parts of society support this action without caring and knowing about the impact of this action, but there are also groups of people who disagree and consider this as an act of violation of the presumption of innocence that must be stopped.